CFD SIMULATION COMPARISON OF BOILER COMBUSTION TEMPERATURE USING CONVENTIONAL COMBUSTION AIR AND OXY-FUEL COMBUSTION - Budiman, Ihsan (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2022)
The burning of fossil fuels is the cause of the largest carbon dioxide (CO2) emissions in the world today. CO2 emissions may cause the greenhouse effect and global countermeasures. Boilers are steam generators that use fossil fuels such as coal and natural gas in their environment. The boiler itself is commonly used in power plants and industrial steam generators. In its operation, conventional boilers fueled by natural gas use air for the combustion system where the content of Nitrogen (N2) gas in ordinary air reaches 79% which dissolves CO2 gas in the exhaust gas so that the CO2 gas is carried into the atmosphere. Several technologies that aim to reduce CO2 emissions include pre-combustion, post-combustion, and combustion of oxygen fuel. Numerical methods such as Computational Fluid Dynamics (CFD) are used because the oxy-fuel technology has limited use in the industrial and utility world, and requires large procurement costs. Based on the simulation results, the combustion temperature in the fire system in 1917 oC originating from the combustion system, the resulting temperature is 1857 oC. Even so, the temperature distribution in the oxyfuel combustion system is more even in the combustion system so that the combustion system will be better. This is evidenced by the comparison of temperature comparison graphs on each furnace wall. The result was an increase in the temperature of the wall furnace by 5 oC to 20 oC.